Parental Involvement in their Young Children’s English Language Learning in a Rural Region of Kazakhstan: A Qualitative Inquiry - Kuspan, Gulbanu (Nazarbayev University Graduate School of Education, 2020)
The integrated curriculum is a recent initiative of the Government of Kazakhstan that includes trilingual education. This reform entails students learning school subjects through three mediums of instruction (Kazakh, Russian, and English) in secondary school. Accordingly, these languages are introduced from the first grade to ensure their successful acquisition. This thesis reports on a qualitative inquiry into Kazakhstani parents’ attitudes towards the introduction of the English language to their young children in Grade 1. It also examines parental challenges in assisting their children with English language learning (ELL), and the strategies used in this regard. In the present study, rural parents’ involvement in their young children’s ELL was investigated to familiarize the public and policymakers with the consequences of implementing the integrated curriculum in Kazakhstan. Semi-structured interviews with 15 rural parents were used to collect data. The findings suggest that almost all parents were aware of the importance of ELL by their children in the modern world. Due to the challenges parents faced in helping their children with ELL, some of them supported the view that their children should have been introduced to the English language at least from the second grade. The findings of this study also reveal that the cooperation between formal and informal social actors (i.e. between teachers and parents) needs to be promoted in Kazakhstan because some parents lack knowledge of English and of effective strategies to prevent their children from being demotivated from learning English. Hence, schools need to become platforms for parents to exchange ideas concerning the best procedures for implementing the trilingual policy and enabling students to actively utilize the English learning resources available to them both inside and outside the classroom. Conducting further mixed methods research which includes the perspectives of parents, teachers, and children themselves would enrich the available database.
Keywords: parental involvement; English language learning; primary school students or children